The Relationship of Audit Quality, Audit Committee, and Sharia Supervisory Board on the Performance of Sharia Commercial Banks in Indonesia - Jihan Irbah Nadiah; Dian Filianti (Universitas Airlangga, 2022)
ABSTRAK Penelitian ini ditujukan untuk mengetahui hubungan kualitas audit, komite audit, dan Dewan Pengawas Syariah (DPS) terhadap kinerja Bank Umum Syariah di Indonesia pada tahun 2015-2020 yang diproksikan dengan ROA, baik secara parsial dan simultan. Melalui pendekatan kuantitatif dengan teknik analisis regresi data panel, hasil penelitian ini menunjukkan bahwa secara parsial, kualitas audit yang dihasilkan KAP Big 4 berpengaruh positif signifikan terhadap kinerja bank umum syariah. Pada variabel komite audit, ukuran komite audit tidak mempengaruhi kinerja bank umum syariah, sedangkan kompetensi dan frekuensi komite audit berpengaruh negatif signifikan terhadap kinerja bank umum syariah. Pada variabel DPS, ukuran dan frekuensi rapat DPS berpengaruh negatif signfikan terhadap kinerja bank umum syariah, sedangkan kompetensi DPS berpengaruh positif signifikan terhadap kinerja bank umum syariah. Secara simultan, kualitas audit, komite audit, serta DPS berpengaruh positif signifikan terhadap kinerja bank umum syariah. Penelitian ini diharapkan dapat bermanfaat bagi manajemen perusahaan, sebagai bahan pertimbangan untuk meningkatkan efektivitas peran pengawasan dalam penerapan tata kelola perusahaan agar dapat mewujudkan kinerja perusahaan menjadi lebih baik. Kata Kunci: Kualitas audit, Komite audit, Dewan Pengawas Syariah, Kinerja Bank. ABSTRACT This study aims is to find out the relationship between audit quality, audit committee, and Sharia Supervisory Board (SSB) on the performance of Islamic Commercial Banks in Indonesia in 2015-2020 as proxied by ROA, both partially and simultaneously. Through a quantitative approach with panel data regression analysis techniques, the results of the study show that partially, the audit quality produced by KAP Big 4 has a significant positive effect on the performance of Islamic commercial banks. In the audit committee variable, the size of the audit committee does not affect the performance of Islamic commercial banks, while the competence and frequency of the audit committee have a significant negative effect on the performance of Islamic commercial banks. In the DPS variable, the size and frequency of DPS meetings have a significant negative effect on the performance of Islamic commercial banks, while DPS competence has a significant positive effect on the performance of Islamic commercial banks. Simultaneously, audit quality, audit committee, and DPS have a significant positive effect on the performance of Islamic commercial banks. This research is expected to be useful for company management, as a consideration for increasing the effectiveness of the supervisory role in the implementation of corporate governance in order to realize better company performance. Keywords: Audit Quality, Audit committee, Shariah Supervisory Board, Banks performance. DAFTAR PUSTAKA Afza, T., & Nazir, M. S. (2014). Audit quality and firm value: A case of Pakistan. Research Journal of Applied Sciences, Engineering and Technology, 7(9), 1803–1810. http://dx.doi.org/10.19026/rjaset.7.465 Al-Sheikh, A. M. A. I. (2005). Tafsir Ibnu Katsir Jilid 2. Surabaya: Pustaka Imam Asy-Syafi’i. Al Farooque, O., Buachoom, W., & Sun, L. (2020). Board, audit committee, ownership and financial performance – emerging trends from Thailand. Pacific Accounting Review, 32(1), 54–81. https://doi.org/10.1108/PAR-10-2018-0079 Alfraih, M. M. (2017). Does ownership structure affect the quality of auditor pair composition? Journal of Financial Reporting and Accounting, 15(2), 245–263. https://doi.org/10.1108/jfra-08-2015-0076 Alharbi, A. T. (2017). Determinants of Islamic banks’ profitability: International evidence. International Journal of Islamic and Middle Eastern Finance and Management, 10(3), 331–350. https://doi.org/10.1108/IMEFM-12-2015-0161 Alqatamin, R. M. (2018). Audit committee effectiveness and company performance: Evidence from Jordan. Accounting and Finance Research, 7(2), 48-60. https://doi.org/10.5430/afr.v7n2p48 Alsartawi, A. M. (2019). Performance of Islamic banks: Do the frequency of Sharīʿah supervisory board meetings and independence matter? ISRA International Journal of Islamic Finance, 11(2), 303–321. https://doi.org/10.1108/IJIF-05-2018-0054 Amine, B. (2018). Contribution of governance to ensure the stability of Islamic banks: A panel data analysis. International Journal of Accounting and Financial Reporting, 8(3), 140–155. https://doi.org/10.5296/ijafr.v8i3.13333 Baidok, W., & Septiarini, D. F. (2017). Pengaruh dewan komisaris, komposisi dewan komisaris independen, dewan pengawas syariah, frekuensi rapat dewan komisaris syariah, dan frekuensi rapat komite audit terhadap pengungkapan indeks Islamic social reporting pada bank umum syariah periode 2010-201. Jurnal Ekonomi Syariah Teori Dan Terapan, 3(12), 1020-1034. https://doi.org/10.20473/vol3iss201612pp1020-1034 Baklouti, I. (2020). Is the Sharia supervisory board a friend or an enemy of Islamic banks? Journal of Islamic Marketing, 13(2), 526–541. https://doi.org/10.1108/JIMA-04-2020-0118 Bank Indonesia. (2009a). Peraturan Bank Indonesia tentang Bank Umum Syariah (Nomor 11/3/PBI/2009). Jakarta: Bank Indonesia. Bank Indonesia. (2009b). Peraturan Bank Indonesia tentang Pelaksanaan Good Corporate Governance bagi Bank Umum Syariah dan Unit Usaha Syariah (Nomor 11/33/PBI/2009). Jakarta: Bank Indonesia. Basiruddin, R., & Ahmed, H. (2020). Corporate governance and Shariah non-compliant risk in Islamic banks: evidence from Southeast Asia. Corporate Governance (Bingley), 20(2), 240–262. https://doi.org/10.1108/CG-05-2019-0138 Billah, F. A. M., & Fianto, B. A. (2021). Pengaruh Islamic corporate governance terhadap kinerja bank syariah: Studi empiris Indonesia dan Malaysia. Jurnal Ekonomi Syariah Teori Dan Terapan, 8(2), 243-254. https://doi.org/10.20473/vol8iss20212pp243-254 Bonita, A. M., & Rahardja, H. (2014). Pengaruh corporate governance terhadap praktik manajemen laba. Diponegoro Journal of Accounting, 3(3), 83-94. Bouaine, W., & Hrichi, Y. (2019). Impact of audit committee adoption and its characteristics on financial performance: Evidence from 100 French companies. Accounting and Finance Research, 8(1), 92-102. https://doi.org/10.5430/afr.v8n1p92 Budiyono, I., & Sabilla, C. K. (2021). Analysis of the influence of audit committee, sharia supervisory board, and Islamic work ethic on the quality of sharia bank financial statements in Indonesia. Al-Arbah: Journal of Islamic Finance and Banking, 3(1), 99–110. https://doi.org/10.21580/al-arbah.2021.3.1.8066 Chapra, U. (2000). Sistem moneter Islam. Jakarta: Gema Insani. Chaudhry, N. I., Roomi, M. A., & Aftab, I. (2020). Impact of expertise of audit committee chair and nomination committee chair on financial performance of firm. Corporate Governance (Bingley), 20(4), 621–638. https://doi.org/10.1108/CG-01-2020-0017 DeAngelo, L. E. (1981). Auditor size and audit quality. Journal of Accounting and Economics, 3(3), 183–199. https://doi.org/10.1016/0165-4101(81)90002-1 Dey, A. (2008). Corporate governance and agency conflicts. Journal of Accounting Research, 46(5), 1143–1181. https://doi.org/10.1111/j.1475-679X.2008.00301.x Glover-Akpey, I., & Azembila, A. B. (2016). The effect of audit committees on the performance of firms listed on the Ghana stock exchange. IOSR Journal of Business and Management, 18(11), 55–62. https://doi.org/10.9790/487X-1811055562 Grassa, R., & Matoussi, H. (2014). Is corporate governance different for Islamic banks A comparative analysis between the Gulf Cooperation Council and Southeast Asian countries. International Journal of Business Governance and Ethics, 9(1), 27–51. https://doi.org/10.1504/IJBGE.2014.062769 Gupta, N., & Mahakud, J. (2021). Audit committee characteristics and bank performance: Evidence from India. Managerial Auditing Journal, 36(6), 813–855. https://doi.org/10.1108/MAJ-04-2020-2622 Haat, M. H. C., Rahman, R. A., & Mahenthiran, S. (2008). Corporate governance, transparency and performance of Malaysian companies. Managerial Auditing Journal, 23(8), 744-778. https://doi.org/10.1108/02686900810899518 Jensen, M. C., & Meckling, W. H. (1976). Theory of the firm: Managerial behavior, agency costs and ownership structure. Journal of Financial Economics, 3(4), 305–360. https://doi.org/10.1016/0304-405X(76)90026-X Kaaroud, M. A., Mohd Ariffin, N., & Ahmad, M. (2020). The extent of audit report lag and governance mechanisms: Evidence from Islamic banking institutions in Malaysia. Journal of Islamic Accounting and Business Research, 11(1), 70–89. https://doi.org/10.1108/JIABR-05-2017-0069 Khalil, A., & Boulila Taktak, N. (2020). The impact of the Shariah Board’s characteristics on the financial soundness of Islamic banks. Journal of Islamic Accounting and Business Research, 11(9), 1807–1825. https://doi.org/10.1108/JIABR-08-2018-0127 Khan, I., & Zahid, S. N. (2020). The impact of Shari’ah and corporate governance on Islamic banks performance: evidence from Asia. International Journal of Islamic and Middle Eastern Finance and Management, 13(3), 483–501. https://doi.org/10.1108/IMEFM-01-2019-0003 Lassoued, M. (2018). Corporate governance and financial stability in Islamic banking. Managerial Finance, 44(5), 524–539. https://doi.org/10.1108/MF-12-2016-0370 Lestari, E., & Murtanto. (2018). Pengaruh efektivitas dewan komisaris, dan komite audit, struktur kepemilikan perusahaan, dan kualitas audit terhadap perataan laba. Jurnal Manajemen Bisnis Krisnadwipayana, 5(1), 97–116. https://doi.org/10.35137/jmbk.v5i1.81 Mansoor, M., Ellahi, N., Malik, Q. A., Attributes, B., & Bank, I. (2019). Corporate governance and credit rating: Evidence of shariah governance from pakistan. International Transaction Journal of Engineering, Management, & Applied Sciences & Technologies. 10(18), 1–11. https://doi.org/10.14456/ITJEMAST.2019.251 Merawati, E. E., & Hatta, I. H. (2014). Pengaruh pengawasan komite audit, audit internal, audit eksternal terhadap kesehatan keuangan perusahaan dan dampaknya terhadap profitabilitas (Atudi pada perusahaan asuransi dan reasuransi yang tercatat di BEI). Jurnal Akuntansi Untar, 18(3), 335–349. Mulyadi, R. (2017). Pengaruh karakteristik komite audit dan kualitas audit terhadap profitabilitas Perusahaan. Jurnal Akuntansi, 4(2), 22–35. https://doi.org/10.30656/jak.v4i2.248 Newell, R., & Wilson, G. (2002). Corporate governance: A Premium for good governance. The McKinsey Quarterly, 3(4), 20–23. Nguyen, Q. K. (2021). Oversight of bank risk-taking by audit committees and Sharia committees: conventional vs Islamic banks. Heliyon, 7(8), e07798. https://doi.org/10.1016/j.heliyon.2021.e07798 Nomran, N. M., & Haron, R. (2019). Dual board governance structure and multi-bank performance: a comparative analysis between Islamic banks in Southeast Asia and GCC countries. Corporate Governance (Bingley), 19(6), 1377–1402. https://doi.org/10.1108/CG-10-2018-0329 Nomran, N. M., Haron, R., & Hassan, R. (2018). Shari’ah supervisory board characteristics effects on Islamic banks’ performance: Evidence from Malaysia. International Journal of Bank Marketing, 36(2), 290–304. https://doi.org/10.1108/IJBM-12-2016-0197 Otoritas Jasa Keuangan. (2015). Peraturan OJK tentang Pembentukan dan Pedoman Pelaksanaan Kerja Komite Audit (Nomor 55/ POJK.04/2015). Jakarta: OJK. Otoritas Jasa Keuangan. (2020). Statistik Perbankan Syariah (Sharia Banking Statistics). Jakarta: OJK. Ramly, Z., Datuk, N., & Nordin, M. (2018). Dewan pengawasan syariah, independensi dewan, risiko komite dan pengambilan risiko bank syariah di Malaysia. Jurnal Internasional Ekonomi Dan Masalah Keuangan, 8(4), 290–300. Riandi, D., & Siregar, H. . (2011). Pengaruh penerapan good corporate governance terhadap return on asset, net profit margin, dan earning per share pada perusahaan yang terdaftar di corporate governance perception index. Jurnal Ekonom, 14(3), 127–133. Rifan, D. F., & Qintharah, Y. N. (2021). Pengaruh kualitas audit dan BOPO terhadap profitabilitas. JRAK: Jurnal Riset Akuntansi Dan Komputerisasi Akuntansi, 12(2), 55–68. http://dx.doi.org/10.33558/jrak.v12i2.2966 Rimardhani, H., Hidayat, R. R., & Dwiatmanto, D. (2016). Pengaruh mekanisme good corporate governance terhadap profitabilitas perusahaan (studi pada perusahaan bumn yang terdaftar di BEI Tahun 2012-2014). Jurnal Administrasi Bisnis, 31(1), 167-175. Rivai, V., Basir, S., Sudarto, S., & Veithzal, A. P. (2013). Commercial bank management: Manajemen perbankan dari teori ke praktik. Jakarta : PT RajaGrafindo Persada. Saeed, M. B., & Saeed, S. K. (2018). Characteristics of shariah supervisory board, corporate governance mechanisms and efficiency of Islamic banks: Evidence from listed banks in Asia. Journal of Islamic Business and Management (JIBM), 8(1), 116–138. https://doi.org/10.26501/jibm/2018.0801-008 Safieddine, A. (2009). Islamic financial institutions and corporate governance: New insights for agency theory. Corporate Governance: An International Review, 17(2), 142–158. https://doi.org/10.1111/j.1467-8683.2009.00729.x Supriyaningsih, S., & Fuad, F. (2016). The influence of audit committee characteristics on real earnings management. Jurnal Akuntansi Dan Auditing, 13(1), 61–79. https://doi.org/10.14710/jaa.13.1.61-79 Ulfa, N. (2019). Analisis pengaruh penerapan good corporate governance terhadap kinerja keuangan bank syariah mandiri tbk tahun 2010-2017. Skripsi tidak dipublikasikan. Tulungagung: UIN SATU Zraiq, M. A., & Fadzil, F. H. (2018). The impact of audit committee characteristics on firm performance: Evidence from Jordan. Scholar Journal of Applied Sciences and Research, 1(5), 39–42.